ANALISIS HASIL BELAJAR PESERTA DIDIK DALAM LITERASI MEMBACA MELALUI STUDI INTERNASIONAL (PIRLS) 2011 - Suryaman, Maman (LITERA, 2015)
Abstract This study aims to describe: (a) Indonesian students’ reading skills in the international level, (b) their skills in solving literary and non-literary test items, and (c) factors affecting their problem solving skills. This study employed the exploratory descriptive approach and document analysis. The data source was the database of IEA Program PIRLS 2011 taken from PIRLS-almanac and TPIRLS-item released. The results of the study are as follows. First, the average attainment of Indonesian students’ reading skills is lower than the international median. Second, their problem solving skills improved from 2006 to 2011, especially in the high, moderate, and low levels, but there was no improvement in the excellent level. Third, the problem solving skills are affected by: (a) a tendency to answer questions by guessing, (b) the poor construction of stems and options, (c) poor quality discourses, (d) reading competence development which is not maximum, (e) inadequate reading habit development, (f) inappropriate literary theories taught, (g) answers which are varied according teachers and students, and (h) test items that do not usually appear in the national examination. Keywords: reading skills, national examination, literary and non-literary test items